Characterization of cold-rolled heterogeneous microstructure formed by multimodal deformation in an Fe-Ni-Al-C alloy with lattice softening. (5th September 2018) - Furuta, Tadahiko; Miyazaki, Izuru; Oh-ishi, Keiichiro; Kuramoto, Shigeru; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract: A heterogeneous microstructure in cold-rolled Fe-24.1Ni-4.06Al-0.43C with lattice softening, where C′  = ( C 11  −  C 12 ) / 2 is significantly reduced, was investigated through hierarchical analysis from the macroscale to nanoscale to determine the origin of the ultrahigh-strength and large ductility of the alloy. Microstructural analysis revealed that the heterogeneous microstructure in the developed Fe-based alloy exhibited a mixture of four kinds of morphology, formed through different deformation processes activated by the specific phase stability with lattice softening which arises at the limit of phase stability of austenite (fcc) phase. In addition to the reduced C′, the alloy is also characterized by the lowered stacking fault energy (SFE) and decreased the austenite-to-martensite (Ms) transformation temperature down to ambient temperature. These results suggest that both deformation twinning and stress-induced martensitic transformation are activated simultaneously or successively, in addition to dislocation glide, during cold rolling in the present alloy. On the basis of microstructural and mechanical characterization of the cold-rolled specimen, it is reasonable to conclude that the work-hardening induced by cold rolling activates a multimodal deformation mechanism which suppresses the premature failure during plastic deformation at ultrahigh-strength. Graphical abstract: Unlabelled Image Highlights: A heterogamous microstructure after cold-rolled of Fe-24.1Ni-4.06Al-0.43C is formed by multi modal deformation. Multi modal deformation is generated by lattice softening, which arises at the limit of phase stability of γ phase. Lattice softening alloy design is significantly reducing C'  = ( C 11 - C 12 )/2 C' . The share stresses of dislocation glide, twin deformation and stress-induced martensite are equal by lattice softening. Multi modal deformation plays an important role in the achievement of ultrahigh yields strength and high ductility.